The land issue on Banggi Island, Sabah, Malaysia: Deagrarianisation and exclusion of the Bonggi - Fadzilah Majid Cooke (Ashgate Publishing Ltd, 2013)
Bonggi communities live on the island of Banggi in northwest Sabah, Malaysia. Livelihood change since the 1960s has ranged from a complete departure from subsistence production in favour of cash crop production to one of spatial and sectoral diversification. This transformation is such that livelihood and income structures may no longer be wholly dependent on agriculture. This paper benefits from debates on deagrarianisation that in general has altered views concerning the contours of poverty including its causes. According to the deagrarianisation perspective, spatial diversification (delocalisation) of livelihoods occurring through ex-situ employment (often via migration) and sectoral diversification through non-farm employment opportunities both in-situ or ex-situ can provide exit conditions that are amenable to an escape from poverty. Notably, Bryceson (2002) has written on deagrarianisation in the African continent, which takes account of the agrarian transition facing many rural areas captured in the transformation of livelihoods and income structures at the household and community levels. These dramatic changes can occur within a generation and belie the seemingly unchanging and stagnant agricultural orientation of the landscape of many rural areas. The changes in the Bonggi so-ecological landscape are documented in a way that demonstrates a people's agency, despite a lack of political representation and voice.